Constraints in goat farming under extensive production system in western Gujarat (Indian Journal of Animal Production and Management, 2018)
The present study was designed to identify the constraints faced by goat farmers under extensive production  system in western Gujarat. Data on problems related to feeding, breeding, health care and marketing  practices were collected using a structured interview schedule (n=90). Problems related to marketing  (56.11%) was observed to be most severe constraint, followed by health care (38.25%), feeding (30.22%)  and breeding (26.30%) constraints. Under feeding constraints, about 68.89% farmers reported scarcity of  drinking water in the study area, but half of the farmers reported severe shrinkage of grazing area (50%).  Breeding constrains such as breeding buck availability, indiscriminate breeding and repeat breeding  problems were classified under low to moderate categories. About 65.56% farmers cited non availability of  any vaccinating agency and classified this problem under more severe category. Goat milk was demanded  less by the consumers (86.67%) and it also fetched lesser price (72.22%) to the farmers. Majority of farmers  (51.11%) reported that no agency helped them for marketing their animals and also the products, hence  travelled longer distances for market. Marketing and health care related constrains were more severe  compared to feeding and breeding constraints in extensive system. Hence, development of proper plan  in goat development programme could augment such constrains under extensive production system.
Keywords: Constraints; Extensive system; Goat farming